‘Teleological mechanics of the mind’: Herbart and Lipps on tendency - Schmidt-Boddy, Philipp (Human studies, 2024)
This article sheds light on a today mostly forgotten though highly influential thinker: Theodor Lipps. It explores the notion of ‘tendency’ in his work, a hitherto insufficiently examined yet central concept of the Munich philosopher. More specifically, the paper examines how Lipps utilizes the term to describe important structures of experience. By illuminating the various ways in which Lipps refers to tendencies, it aims to reconstruct important pillars of his theory of experience. This theory emphasizes that experience has a teleological character, striving towards the complete determination and realization of the objects as they are represented (vorgestellt) in our experience. As will be shown, the description of different tendencies serves Lipps to conceptualize the laws that govern the related dynamics of our psychic life and to distinguish and examine the diverse range of conscious phenomena within it. To unveil the core ideas that guide Lipps’s development of his proposal, the article will first identify and reconstruct the primary source for his philosophical analysis of the mind’s motions: the metaphysics of Johann Friedrich Herbart. Subsequently, Lipps’s critical examination of Herbart’s proposal will be presented. This discussion will serve as a backdrop to illustrate how Lipps integrates Herbartian themes, reformulates related concepts, and ultimately develops his unique understanding of tendency and its roles in experience. By delving into his comprehensive analysis of tendencies, it will be argued that Lipps offers a version of Herbartianism.
Online veröffentlicht: 17. Juni 2024
Gesehen am 18.11.2024